Employment conditions and work-related stressors are associated with menopausal symptom reporting among perimenopausal and postmenopausal women. Issue 3 (March 2017) - Bariola, Emily; Jack, Gavin; Pitts, Marian; Riach, Kathleen; Sarrel, Philip
Abstract: Objective: While many women undergo menopausal transition while they are in paid employment, the effect of poor working conditions on women's experience of the menopause has received scant empirical attention. We examined associations between employment conditions, work-related stressors, and menopausal symptom reporting among perimenopausal and postmenopausal working women. Methods: Data were drawn from an online survey conducted between 2013 and 2014 involving 476 perimenopausal and postmenopausal women working in the higher education sector in Australia. Survey questions assessed demographics; health-related variables; menopausal symptom reporting; employment status; presence of flexible working hours; presence of temperature control; job autonomy; and supervisor support. Results: A forced entry multivariable regression analysis revealed that high supervisor support (β = −0.10, P = 0.04), being employed on a full-time basis (β = −0.11, P = 0.02), and having control over workplace temperature (β = −0.11, P = 0.02) were independently associated with lower menopausal symptom reporting. Conclusions: These findings may help inform the development of tailored occupational health policies and programs that cater for the needs of older women as they transition through menopause in the workplace.